2014
DOI: 10.1130/b31040.1
|View full text |Cite
|
Sign up to set email alerts
|

Crustal attenuation as a tracer for the emplacement of the Beni Bousera ultramafic massif (Betico-Rifean belt)

Abstract: The study of petrology (fi eldwork, petrography, and phase diagram modeling) and structural data of the metapelitic granulites and the southern, high-temperature exposed peridotites in the Beni Bousera massif (northern Morocco), combined with results from previous regional studies of the Alborán, suggest a new emplacement mechanism for the mantle rocks in the Betico-Rifean belt. We document two key metamorphic episodes in the granulites within a temperature window of 710-830 ± 50 °C: (1) An earlier prograde hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 74 publications
(75 reference statements)
1
12
0
Order By: Relevance
“…Asymmetric aureoles can be explained by incremental emplacement (Figure 10) or by the presence of a fault on one side of the pluton along which the intrusion has been exhumed (Alvarez-Valero et al, 2014). Interestingly, higher temperatures at the roof than at the floor are reported for Skaeregaard mafic intrusion (Bufe et al, 2014) whereas the opposite is true for Manaslu leucogranite intrusion (Guillot et al, 1995).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Asymmetric aureoles can be explained by incremental emplacement (Figure 10) or by the presence of a fault on one side of the pluton along which the intrusion has been exhumed (Alvarez-Valero et al, 2014). Interestingly, higher temperatures at the roof than at the floor are reported for Skaeregaard mafic intrusion (Bufe et al, 2014) whereas the opposite is true for Manaslu leucogranite intrusion (Guillot et al, 1995).…”
Section: Discussionmentioning
confidence: 86%
“…Several asymmetric aureoles have been reported (Guillot et al, 1995;Alvarez-Valero et al, 2014;Bufe et al, 2014). Asymmetric aureoles can be explained by incremental emplacement (Figure 10) or by the presence of a fault on one side of the pluton along which the intrusion has been exhumed (Alvarez-Valero et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the metamorphic and tectonic study of the Nieves sedimentary unit in the footwall of the Ronda peridotite thrust provides independent constraints to a hot emplacement of the Ronda peridotites after the Aquitanian (metamorphosed sediments of Aquitanian ages below the peridotites; Martín‐Algarra, ; Mazzoli et al, ). A fast switch from extension (between 30 and 21 Ma) to thrusting (at 21 Ma) has therefore been proposed to explain the thrusting of the Ronda peridotites onto the Iberian/Moroccan margin (Álvarez‐valero et al, ; Frasca et al, ).…”
Section: Geological Settingmentioning
confidence: 99%
“…2D). Most authors currently adopt similar views in describing a long-term exhumation of the Ronda-Beni Bousera peridotites (Afiri et al, 2011;Précigout et al, 2013;Álvarez-Valero et al, 2014;Hidas et al, 2015;Gueydan et al, 2015;Gervilla et al, 2019). However, Rossetti et al (2010Rossetti et al ( , 2020 and Melchiorre et al (2017) demonstrated that the Beni Bousera peridotites were exhumed to lower-crust depth during the waning stage of the Hercynian orogeny.…”
Section: Introductionmentioning
confidence: 92%